The main tendencies of translating phraseologisms with ethnocultural components - Bebko, Svitlana (My University, 2017)
The article features the theoretical approaches to the notion of ethnocultural component and its functions. There has been distinguished the main sources of ethnospecific images. There has been considered the main ways of translating phraseological units with ethnocultural component.
Keywords: phraseologism; ethnocultural component; imagery; pragmatic meaning; фразеологізм; етнокультурна; образність; кафедра ділової іноземної мови та міжнародної комунікації